Smoking relapse prevention: abstinence, relapse, current practice and effective interventions - Agboola, Shade (2017)
Smoking remains a major cause of morbidity and mortality. In 2013/2014, 454,700 hospital admissions in the UK amongst persons 35 years and over were estimated to be attributable to smoking. This accounts for 4 per cent of all hospital admissions in this age group. In 2013, 17% (78,200) of all deaths in adults aged 35 and over were estimated to be caused by smoking[1]. Reducing smoking therefore, remains a major priority for governments and health systems like the UK National Health Service (NHS). Following the publication of the Government’s White Paper, Smoking Kills[2] in 1998, a comprehensive tobacco control strategy was implemented. This strategy was aimed at reducing uptake of smoking and increasing quitting among existing smokers, and involved a combination of population tobacco control interventions (such as price rises, an advertising ban and smoke-free legislation) combined with treatment for dependent smokers through the NHS. A Tobacco Control Plan for England was also produced in 2011 which explained the government’s strategy to reduce smoking through the new public health system[3]. This plan outlined commitments to implement legislation to end display of tobacco in shops, to encourage smokers to quit and remaining quit by using effective forms of support and implementing a policy of using tax to maintain the high price of tobacco. Effective forms of support may be behavioural, pharmacological or a combination of both[3]. In the UK, support is often delivered by stop smoking services (SSS), although smokers, who wish to, may obtain smoking cessation medication from their GP[4]. These SSS have been shown to be cost effective, but the majority, 85% of smokers attending the services, have relapsed by one year. The nature of nicotine addiction means that smoking is a chronic relapsing condition[5], with many smokers unable to sustain abstinence. Smoking relapse rates can be extremely high (up to 90% in the first 3 months)[6], and only 3%-5% of unsupported/untreated quitters maintain their quit attempt for 6 months or longer[7]. This high relapse rate reflects the addictive nature of cigarette smoking and underscores the importance of finding effective relapse prevention interventions for use in routine practice, which can be delivered alongside or after acute cessation has ended. There is no universally accepted definition of what interventions to prevent relapse to smoking (relapse prevention interventions - RPIs) should comprise; many smoking cessation programmes simply modify the content of existing, cessation-orientated support and deliver these as relapse prevention[8]. The paucity of information regarding provision of smoking relapse prevention is in contrast to the wide availability of evidence for the use of acute cessation treatments which has grown rapidly over recent decades. A variety of effective treatments now exist which can increase the chances of stopping smoking up to fourfold compared with no support[9], but research suggests that relapse prevention interventions and treatments are not as widely known or even used. At the time the research was conceived, there was very little information about the effectiveness of RPIs. A number of studies had investigated effectiveness of behavioural support, pharmacotherapies, and combination treatments, as forms of relapse prevention or maintenance treatment, and one Cochrane Review[8] found no evidence for the effectiveness of behavioural RPIs, but this may have been because the review combined smoking outcomes obtained at different follow-up time points after quitting and this may have obscured real effects of RPIs. The review found insufficient evidence for the effectiveness of extended treatment with bupropion and weak evidence for the effectiveness of nicotine replacement therapy for relapse prevention. There was, therefore, a need to examine current literature and synthesize data from a wide variety of studies, using a different approach from that used in the Cochrane Review to enhance interpretation of findings. In addition to ascertaining whether or not RPIs are effective, there was also a need to explore feasibility of provision within local Smoking Cessation Services. No study had explored feasibility of provision of RPIs within Stop Smoking Services, and whether these interventions would be acceptable to smokers trying to quit, mainly because the use of relapse prevention interventions in a local smoking cessation service was not only relatively new and unproven, there was also no information regarding smokers’ perceptions of relapse prevention interventions Abstinence and relapse during a quit process is still poorly understood, especially relapse after the use of a smoking cessation aid. A few studies had investigated patterns of relapse and abstinence in smokers who quit smoking unaided and two reviews[7 10] found that the majority of relapse occurred in the first two weeks of starting a quit attempt. The majority of smokers who wish to quit smoking use some form of evidence based treatment. It was therefore important to explore patterns of relapse in smokers who have attempted to quit smoking with the aid of a smoking cessation treatment. The work presented here is for the degree of PhD by publication and is based upon five publications in high quality peer reviewed journals between 2009 and 2015. I am the lead author on four of the included papers and the final and corresponding author on one paper. The research forms a coherent body of work informing the evidence base on smoking relapse prevention interventions (RPIs). This has contributed to the evidence base around four key aspects of smoking relapse prevention: knowledge, views and beliefs, effectiveness of smoking relapse prevention interventions, feasibility of delivery of RPIs within UK Stop Smoking Services, and abstinence and relapse patterns amongst smokers who quit smoking with the aid of a pharmacological smoking cessation treatment. Systematic reviews, meta-analysis, quantitative research and qualitative research were used to generate the data which supported the exploration of the four themes outlined below. Specifically, the published works have identified: • Knowledge, Understanding, Views and Beliefs: there was no shared understanding of what relapse prevention meant to Stop Smoking Service professionals or the kinds of interventions that should be used for this, but a willingness to provide such treatments was apparent. (Agboola SA, Coleman, T and McNeill, A. (2009). Relapse prevention in UK Stop Smoking Services: a qualitative study of health professionals' views and beliefs. BMC Health Services Research. 9:67 and Agboola SA, Coleman TJ, Leonardi-Bee J, McEwen A and McNeill A (2010). Provision of relapse prevention interventions in UK NHS Stop Smoking Services: a survey. BMC Health Services Research 10:214)